The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/clc.23428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasons on the management and outcomes acute myocardial infarction: An 18‐year US study

Abstract: Background: There are limited data on the seasonal variation in acute myocardial infarction (AMI) in the contemporary literature. Hypothesis: There would be decrease in the seasonal variation in the management and outcomes of AMI. Methods: Adult (>18 years) AMI admissions were identified using the National Inpatient Sample (2000-2017). Seasons were classified as spring, summer, fall, and winter. Outcomes of interest included prevalence, in-hospital mortality, use of coronary angiography, and percutaneous coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…1 C and D). AMI-CS admissions with respiratory infections had significantly longer length of hospital stays (12 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 vs 6 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 days), higher hospitalization costs and were less likely to be discharged home (27.1% vs 44.7%) compared to admissions without respiratory infections ( Table 2 ). Sensitivity analyses revealed similarly lower in-hospital mortality for admissions with respiratory infections across all sub-groups of interest ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 C and D). AMI-CS admissions with respiratory infections had significantly longer length of hospital stays (12 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 vs 6 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 days), higher hospitalization costs and were less likely to be discharged home (27.1% vs 44.7%) compared to admissions without respiratory infections ( Table 2 ). Sensitivity analyses revealed similarly lower in-hospital mortality for admissions with respiratory infections across all sub-groups of interest ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to prior literature, we defined the seasons based on the meteorological classification of the Northern Hemisphere as–Spring (March–May), Summer (June–August), Fall (September–November) and Winter (December-February). 18 , 19 Chronic lung disease was identified using Charlson Comorbidity Index codes ICD-9CM 416.8, 416.9, 490. x-505. x, 506.4, 508.1, 508.8 and ICD-10 CM I27.8, I27.9, J40.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern depends on the specific daily time period, levels of car traffic, places of residence and commuting throughout the city, and other epidemiologic and demographic factors [ 19 ]. Sudden myocardial infarctions, for example, follow a regular pattern of occurrence [ 24 27 ], with most events occurring between morning and noon [ 28 , 29 ]. Moreover, some studies report seasonal or weekly patterns of occurrence of myocardial events, with a reported increase on Mondays [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%